Role of mesenchymal stem cells and their culture medium in alleviating kidney injury in rats diabetic nephropathy - Amal Al-Shahat Ibrahim; Manal Mohammad Morsy; Safwat E. Abouhashem; Omnia Aly; Norhan A. Sabbah; Nermin Raafat (Egyptian Journal of Medical Human Genetics, 2020)
Abstract Background Diabetic nephropathy (DN) is considered as one of the most serious complications resulting from diabetes mellitus and end-stage of renal failure globally. Up to 40% of diabetic patients will develop DN. The involvement of mesenchymal stem cells (MSCs) in diabetic renal lesions management has been established in many animal models of DN. The aim is to evaluate the capability of MSCs and their culture medium (CM) to alleviate DN in streptozotocin (STZ)-induced diabetic rat model. Female albino rats were made diabetic and were further categorized into 4 subgroups of 15 each: DN group, DN group received fibroblasts, MSCs group received one dose of 1 × 106 cells of MSCs, and CM group received one dose of 500 μl of CM. In all groups, the treatment was delivered by intravenous injection (IV) into the tail vein. Results MSCs insinuated themselves into the injured kidney as detected by CD44 expression. Biochemical and histological results showed that MSCs and/or CM effectively attenuated DN manifestations in rat model through their possible anti-inflammatory (tumor necrosis factor-α and transforming growth factor-β1 were decreased), anti-apoptotic (Bcl2 was increased while Bax and caspases were decreased), and anti-oxidant role (malondialdehyde was decreased while glutathione and catalase were increased). Conclusion These results provide a potential therapeutic tool for DN management through the administration of the CM from MSCs that ameliorates the effects of diabetes. It is also possible to treat DN using CM alone thus avoiding cell transplantation.